PENGARUH RASIO PASAR, PROFITABILITAS, AKTIVITAS, DAN SOLVABILITAS TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN ECERAN DI BEI) - B31111100, YOTIE (Jurnal Manajemen Update, 2016)
This research aim to examine the effect of market ratios (EPS), profitability (ROA), activity (TATO), and solvability (DER) to Stock Return in the Sub Sector Retail Trade Company (retail trade) at the Indonesian Stock Exchange (IDX), during the period 2010 to 2014. The population that becomes the object in this research is a sub company of the retail trade sector (retail trade) that listed in (IDX). The samples used were 15 companies which presented financial statements in accordance with sample selection criteria. The amount of data of 75 observations was analyzed using linear regression.               The result of this research indicates that not finding variable that deviates from the classical assumption so that the requirement for doing multiple linear regression analysis has been fulfilled. Based on the results of the F test (simultaneous) showed that the regression model which built had fulfilled the specification of the model eligibility (goodness of fit model test) with a probability value (significance) 0.001. Furthermore, the result of t test showed that the variable solvability ratio (DER) has a negative impact and significant on stock return and variable activity ratio (TATO) has a positive impact and significant on stock return, while the profitability ratio (ROA) and market ratio (EPS) do not have a significant impact on stock return. The result of Coefficient Determination (Adjusted R2) showed that only 21.9% of the variation ROA, EPS, TATO, and DER can explain the variation of stock return while the rest described by the other factor which is not examined in this research. Keywords: Earning Per Share (EPS), Return on Asset (ROA), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO), Stock Return.